PENGARUH FINANCIAL DISTRESS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP KONSERVATISME AKUNTANSI: (Studi Kasus Pada Perusahaan Manufaktur Sektor Industri Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Pertiwi, Sri Wulan; Nensi Yuniarti. Zs; Furqonti Ranidiah; Yudi Partama Putra; Chairul Suhendra (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of financial distress, leverage, and company size on accounting conservatism in manufacturing companies in the food and beverage industry sector which are listed on the Indonesia Stock Exchange in 2019-2021. This study uses secondary data in the form of industrial (company) financial reports for the food and beverage sector for 2019-2021. The study used the purposive sampling method, with the number of companies 25 x 3 years of research and a total sample of 75. The statistical method used was SPSS multiple linear regression with hypothesis testing, partial t statistical test, simultaneous f test and test of the coefficient of determination. The results of this study indicate that: based on the results of the t test for the variable financial distress (X1_FD) it has a significance of 0.155, which means that it is greater than 0.05, then H1 is rejected. Thus it can be concluded that the financial distress variable has no significant effect on accounting conservatism. The leverage variable (X2_LEV) has a significance of 0.000, which means it is smaller than 0.05, then H2 is accepted. Thus it can be concluded that the leverage variable (X2_LEV) has a significant effect on accounting conservatism. And the results of testing hypothesis 3 show that firm size (X3_UP) has no effect on accounting conservatism. This can be seen from the significance value of 0.491. The significance level is above 0.05, so it can be concluded that company size has no effect on accounting conservatism.